2013
DOI: 10.1186/1472-6963-13-482
|View full text |Cite
|
Sign up to set email alerts
|

Micro-costing the provision of emotional support and information in UK eye clinics

Abstract: BackgroundSight loss has wide ranging implications for an individual in terms of education, employment, mobility and mental health. Therefore there is a need for information and support to be provided in eye clinics at the point of diagnosis of sight threatening conditions, but these aspects of care are often missing from clinics. To meet these needs, some clinics employ an Eye Clinic Liaison Officer (ECLO) but the position has yet to be widely implemented. The aims of this study were:(1) To evaluate the forms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 14 publications
(18 reference statements)
0
9
0
Order By: Relevance
“…Whilst costing is complex and would need to take into account other factors, the underlying principle here is that this would be significantly less than the cost of a clinical consultation. Recognising the need for the ECLO service and the provision of appropriate funding by commissioners are important steps towards the provision of equal levels of care throughout the UK . Furthermore, it has been suggested that ECLOs may expand their services to provide patients with appropriate clinical information about sight threatening conditions at the point of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Whilst costing is complex and would need to take into account other factors, the underlying principle here is that this would be significantly less than the cost of a clinical consultation. Recognising the need for the ECLO service and the provision of appropriate funding by commissioners are important steps towards the provision of equal levels of care throughout the UK . Furthermore, it has been suggested that ECLOs may expand their services to provide patients with appropriate clinical information about sight threatening conditions at the point of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been suggested that ECLOs may expand their services to provide patients with appropriate clinical information about sight threatening conditions at the point of diagnosis. We would caution against this as patients often request specific clinical information, and the provision of inaccurate or generic information may be detrimental . Clinical information should be made widely available in the eye clinics in the form of leaflets, DVDs, or taped recordings as this aspect of care may be missing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations